The relationship between home environment and self-management towards academic performance of private institution students in Kuala Lumpur - S., Komlavathi; Yasin, Maizura (Macrothink Institute, 2022)
Education plays an important role in providing a better life for students, and learning starts at home, specifically since they are born. This study investigated the effect of home environment and self-management on students’ academic performance at a private institution in Kuala Lumpur using descriptive and Pearson correlation analysis. The focus of the study s to find out the relationship between economic status, family involvement, home infrastructure, parenting style, self-management, and academic performance. This study involved 145 students, and data were collected using a questionnaire containing 4 parts: demographic, home environment, self-management, and academic performance. The data were analysed using Microsoft Excel. The data revealed a positive correlation between home environment, self-management, and academic performance. The results also showed that educational institutions must focus on students’ self-management to improve their academic performance. Furthermore, there is a need to look at students’ home environment, such as parenting style, family involvement, and home infrastructure, to encourage parental support toward improving students’ academic performance.